Therapeutic Efficacy and Fate of Bimodal Engineered Stem Cells in Malignant Brain Tumors1. (23rd August 2013) - Martinez‐Quintanilla, Jordi; Bhere, Deepak; Heidari, Pedram; He, Derek; Mahmood, Umar; Shah, Khalid
Abstract Therapeutically engineered stem cells (SC) are emerging as an effective tumor‐targeted approach for different cancer types. However, the assessment of the long‐term fate of therapeutic SC post‐tumor treatment is critical if such promising therapies are to be translated into clinical practice. In this study, we have developed an efficient SC‐based therapeutic strategy that simultaneously allows killing of tumor cells and assessment and eradication of SC after treatment of highly malignant glioblastoma multiforme (GBM). Mesenchymal stem cells (MSC) engineered to co‐express the prodrug converting enzyme, herpes simplex virus thymidine kinase (HSV‐TK) and a potent and secretable variant of tumor necrosis factor apoptosis‐inducing ligand (S‐TRAIL) induced caspase‐mediated GBM cell death and showed selective MSC sensitization to the prodrug ganciclovir (GCV). A significant decrease in tumor growth and a subsequent increase in survival were observed when mice bearing highly aggressive GBM were treated with MSC coexpressing S‐TRAIL and HSV‐TK. Furthermore, the systemic administration of GCV post‐tumor treatment selectively eliminated therapeutic MSC expressing HSV‐TK in vitro and in vivo, which was monitored in real time by positron emission‐computed tomography imaging using 18F‐FHBG, a substrate for HSV‐TK. These findings demonstrate the development and validation of a novel therapeutic strategy that has implications in translating SC‐based therapies in cancer patients. STEM Cells2013;31:1706–1714